Range of confining pressures for the Hoek–Brown criterion. Issue 4 (17th February 2016) - Latapie, Benoît; Lochaden, Andrew L. E.
Abstract : Engineering in weak rock using modern, computer-based design techniques is notoriously challenging because the laboratory tests and classification methods routinely carried out on such materials yield rock parameters. Such parameters are not directly compatible with the most widely used constitutive model of those computer-based methods – that is, the Mohr–Coulomb failure envelope. There is no direct relationship between Mohr–Coulomb (linear) and Hoek–Brown (non-linear) parameters, and marrying those two failure envelopes is notoriously difficult. When formulating a failure criterion for rock materials, based on rock and rock mass parameters, a correlation with the Mohr–Coulomb failure criterion has been proposed, which can be obtained from the computer program RocLab. One of the essential input parameters for such correlation is called the maximum confining pressure. This parameter directly affects the correlated shear strength parameters on the Mohr–Coulomb failure envelope and hence choosing it with care is the key to producing a safe, yet economic design. The present paper discusses the use of several methods for determining the maximum confining pressure to derive Mohr–Coulomb parameters for weak rock in slope and retaining wall applications. The suitability of each method considered is discussed against the results of back analyses, and design recommendations are proposed.